A study on social intelligence with special reference to Technical Education (Journal of Advances and Scholarly Researches in Allied Education, 2024)
This study explores the role of social intelligence in the context of technical education, highlighting its importance for students pursuing technical fields. Social intelligence, defined as the ability to effectively navigate and negotiate complex social relationships and environments, is crucial in the collaborative and dynamic world of technical professions. Through a mixed-methods approach, incorporating surveys, interviews, and observational studies, the research examines the levels of social intelligence among technical education students and the impact of this intelligence on their academic and professional performance. The findings suggest that higher levels of social intelligence correlate with better teamwork, enhanced communication skills, and increased adaptability in technical settings. The study also identifies key factors that influence the development of social intelligence, including educational curriculum, extracurricular activities, and the learning environment. Recommendations for integrating social intelligence training into technical education programs are provided, aiming to prepare students for the interpersonal demands of their future careers.